Ultraviolet imaging observations of three jellyfish galaxies: star formation suppression in the centre and ongoing star formation in stripped tails. Issue 2 (8th December 2022) - George, K; Poggianti, B M; Tomičić, N; Postma, J; Côté, P; Fritz, J; Ghosh, S K; Gullieuszik, M; Hutchings, J B; Moretti, A; Omizzolo, A; Radovich, M; et al.
ABSTRACT: Spiral galaxies undergo strong ram-pressure effects when they fall into the galaxy cluster potential. As a consequence, their gas is stripped to form extended tails within which star formation can happen, giving them the typical jellyfish appearance. The ultraviolet imaging observations of jellyfish galaxies provide an opportunity to understand ongoing star formation in the stripped tails. We report the ultraviolet observations of the jellyfish galaxies JW39, JO60, JO194 and compare with observations in optical continuum and Hα. We detect knots of star formation in the disc and tails of the galaxies and find that their UV and Hα flux are well correlated. The optical emission line ratio maps of these galaxies are used to identify for every region the emission mechanism, due to either star formation, LINER or a mix of the two phenomena. The star-forming regions in the emission line maps match very well with the regions having significant UV flux. The central regions of two galaxies (JW39, JO194) show a reduction in UV flux which coincides with composite or LINER regions in the emission line maps. The galaxies studied here demonstrate significant star formation in the stripped tails, suppressed star formation in the central regions and present a possible case of accelerated quenching happening in jellyfish galaxies.